2015
DOI: 10.1017/s1751731115000348
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Rosemary extract in the diet of Nero Siciliano pigs: evaluation of the antioxidant properties on meat quality

Abstract: In the present study, the effect of Rosmarinus officinalis L. dietary supplementation on meat quality and oxidative stability of Nero Siciliano pigs was examined. During the growing-fattening period, 32 Nero Siciliano pigs were allotted into two treatment groups consisting of 8 replicates with 2 pigs per pen. For 90 days, the animals received a basal diet: one group (CTR) was not dietary supplemented, whereas the other group received (1 g/kg) rosemary extract (ROX). Supplementation with rosemary extract signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…From the health point of view, although a higher polyunsaturated fatty acids (PUFA)/saturated fatty acids (SFA) ratio in pork is desirable, the pork become more prone to oxidation and leading to deterioration of flavour (Guo et al, ). Several studies confirmed that improvement of antioxidative capacity has beneficial effects on meat shelf life and pork quality (Liotta, Chiofalo, & D'alessandro, Presti & Chiofalo, ; Lu et al, ; Ma, Lin, et al, ; Zhang et al, ). Ramie may be an alternative and healthy ingredient with good palatability and nutrition for swine diet (Kipriotis et al, ), but it is underutilized at the present.…”
Section: Introductionmentioning
confidence: 86%
“…From the health point of view, although a higher polyunsaturated fatty acids (PUFA)/saturated fatty acids (SFA) ratio in pork is desirable, the pork become more prone to oxidation and leading to deterioration of flavour (Guo et al, ). Several studies confirmed that improvement of antioxidative capacity has beneficial effects on meat shelf life and pork quality (Liotta, Chiofalo, & D'alessandro, Presti & Chiofalo, ; Lu et al, ; Ma, Lin, et al, ; Zhang et al, ). Ramie may be an alternative and healthy ingredient with good palatability and nutrition for swine diet (Kipriotis et al, ), but it is underutilized at the present.…”
Section: Introductionmentioning
confidence: 86%
“…Studies available in the literature and considered in this manuscript indicate that the age at slaughter for the SB breed ranges from 169 to 730 days of age [32][33][34][35][36], with a live body weight from 62 to 121 kg [37][38][39][40][41]. According to the SEUROP classification (classification of carcasses defined by the European Union) [42], the yield of dressing was about 80%, and lean meat content ranged from 39.7% to 59.0% [38][39][40][41]. In addition, the BFT value measured was 52 mm at the withers, from 17 to 49 mm at the last rib, and from 30 to 49 mm above the gluteus medius muscle [32,33,35,40].…”
Section: Productive Characteristicsmentioning
confidence: 99%
“…The chemical characteristics of olive cake, totally pitted, used in the trial were determined according to AOAC methods [22], and the fatty acid methyl esters (FAME) were analyzed by GC-FID, following the procedure described below [23]. The analysis of each parameter was replicated three times for each by-product, and the results were reported as a mean of the three replications (Table 1).…”
Section: Animals Facilities and Experimental Dietsmentioning
confidence: 99%
“…Table 3 shows the nutritional characteristics and energy content of the diets. Samples of the dietary treatments were analyzed to determine the chemical composition [22] and the fatty acid profile (Table 4), following the procedure described below [23]. Each parameter was analyzed three times for each dietary treatment; Tables 3 and 4 show the mean values of the three analyses.…”
Section: Dried Olive Cakementioning
confidence: 99%
See 1 more Smart Citation